The Political Necessity of Transpersonal Work Deep Democracy's Potential to Transform Polarized Conflicts - Rowek, Marcella (Masters of Peace,, 2018)
Marcella Rowek explores the paradigm of Deep Democracy and its potential to transform polarized conflicts in the context of the current refugee situation in Europe. Her approach to peace work and research is embedded in the Innsbruck School of Peace Studies' philosophy of Transrational Peaces and Lederach's Elicitive Conflict Transformation. At the heart of a deeply democratic attitude is the idea that all perspectives, experiences, feelings, body sensations and awareness levels of the conflicting parties have to be acknowledged and consciously worked with. Only then conflict transformation processes can unfold. This is linked to a systemic and transpersonal perspective, which assumes that not a single person, event or group triggers a conflict, but that it is systemically co-created. Contents Field Theories Transpersonal Psychology Conflict Transformation Worldwork Case Study Zurich Target Group Lecturers and students in the field of peace and conflict studies, reconciliation, psychology, political science and social medicine Practitioners and researchers in the field of peace work, mediation, education, community work, psychotherapy, social work The Author Marcella Rowek is a peace researcher from the MA program in Peace, Development, Security and International Conflict Transformation at the University of Innsbruck. She strives for a culture of creativity and transrationality in community processes.